The Effects of Delays in Algerian Construction Projects: an Empirical Study - Salhi, Roumeissa; Messaoudi, Karima (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper examines the effects of delays in the Algerian construction industry in order to identify the various critical aspects of the causes for improving the economy in the construction sector. A questionnaire survey was conducted to assess the perceptions of all players in the construction industry, which led to the identification of the most significant impacts of delays.
Keywords: construction management; construction delay; effects of delays; time control; SMART-PLS; Algieria; zarządzanie budową; opóźnienie budowy; skutki opóźnień; kontrola czasu